Dry season rainfall as a source of transpired water in a seasonal, evergreen forest in the western Amazon region inferred by water stable isotopes - Borma, Laura De Simone; Demetrio, Wilian Carlo; Souza, Ranieli Dos Anjos De; Verhoef, Anne; Webler, Alberto; Aguiar, Renata Gonçalves (Frontiers in Water, 2022)
The present work aimed to investigate the potential sources of water for plants in an area of evergreen forest located in western Amazonia (Rebio Jaru). We used natural abundance of water isotopes - δ2H and δ18O - to trace the main source of water to plants in the beginning of the dry period (May 2016) and in the end of the dry period/transition to the wet period (October 2016) following a severe El Niño drought (ENSO 2015/16). Soil samples were collected in a soil profile up to 4 m depth. Plant samples from 18 trees (14 species) were collected in May and in October 2016. Rainwater and river water samples were collected between September 2015 and February 2017. We found that, at the end of the dry period/transition to the wet period (i.e., October 2016), the average plant xylem signal was more enriched (δ2H: -20.0 ± 8.1 ‰; δ18O: -1.13 ± 1.88 ‰) than in May 2016 (δ2H: -36.7 ± 5.6 ‰; δ18O: -3.50 ± 1.30 ‰), the onset of the dry period. The averaged isotopic soil signal in May 2016 (δ2H: -35.4 ± 5.90 ‰; δ18O: -5.19 ± 0.70 ‰) is slightly more depleted than in October (δ2H: -27.6 ± 13.8 ‰; δ18O: -4.35 ± 1.73 ‰) and, in general, more depleted than the xylem signal. In the dual isotope space, the xylem signal at the beginning of the dry period follows the rainfall signal of the wet period, while the xylem signal at the end of the dry period/transition to wet period follows the signal of the dry season rainfall, suggesting plants mostly transpires a most recent rainwater. Contrary to what was expected, we did not find evidence in the xylem signal of the water stored in the soil pores, which suggests that, to attend the water demands of the dry period, plants do not use the water from past periods stored in the soil layers.